Influences of Groove Geometries on Bend Radius and Springback in V-Bending - Banh, Quoc-Nguyen; Le, Viet-Khai; Le, Anh-Chuong; Tran, Anh-Son; Ho, Minh-Tuan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Investigation of the V-bending process with the effect of V-grooving insert geometries is performed through finite element analysis within ANSYS LS-DYNA. Different V-groover geometries are tested to evaluate the effect on the final bent angle and bent radius of the sheet metal part, with the objective of obtaining the minimized bent angle and bent radius results. It is also observed that the corner radius of the V-groover has a major influence on the bent angle and bent radius. Due to the removal of material in the bending region, which reduced the bending resistance, an increase in the corner radius results in a decrease in both the bent angle and radius. The shape of V-groover also affects the bending results, with variations in geometries leading to variations in both bent angle and radius. When the cutting cross-sectional area is kept constant, the bent angle shows minimal variation, while the bent radius steadily increases with the V-groover angle, reaching its maximum at 90 degrees.